Analyzing Motor Vehicle Restriction Policies: A Comparative Study of Indonesia and Japan - Riswanda, Lavica Anky (Jurnal Mengkaji Indonesia, 2024)
Abstract: The rapid increase in motorized vehicles in developing countries, particularly in Asia and Latin America, poses significant challenges, including congestion, pollution, and road accidents. In Indonesia, the high growth rate of motorized vehicles, especially in Jakarta, exacerbates these issues, prompting the implementation of policies such as odd-even restrictions. In contrast, Japan has adopted a comprehensive approach with strict regulations on vehicle ownership, high taxes, and expensive parking fees. Purpose: This research aims to conduct a comparative analysis of motor vehicle restriction policies in Japan and Indonesia. By examining the policy formulation process, the study seeks to identify the determinants, key actors, and impacts of these policies. The purpose is to provide insights into how different factors influence government actions in responding to the challenges posed by the growing ownership of motorized vehicles. Design/Methodology/Approach: The research employs a comparative public policy approach, systematically analyzing political processes in both countries. The study focuses on the stages of policy formulation, specifically from agenda setting to policy evaluation. Through this conceptual framework, the research identifies external and internal factors, goals, and key actors shaping online transportation policies in Japan and Indonesia. Findings: In Japan, the central government, through the Ministry of Land, Infrastructure and Transport, implements strict regulations on vehicle ownership, including high taxes, mandatory testing, and expensive parking fees. This centralized approach effectively controls private vehicle ownership. In Indonesia, the DKI Jakarta Provincial Government's odd-even policy faces criticism for being partial and lacking preventive measures, resulting in potential violations and congestion shifts. The lack of synchronization between central and local governments also hampers policy effectiveness. Originality/value: This research contributes to understanding the effectiveness of motor vehicle restriction policies by comparing the approaches taken in Japan and Indonesia. The findings provide valuable insights for policymakers, highlighting the importance of a holistic and preventive approach involving both upstream and downstream measures to address challenges related to massive vehicle ownership.